Audio-cued motor imagery-based brain–compute rinterface: Navigation through virtual and real environments - Velasco-Álvarez, Francisco Javier; Ron-Angevin, Ricardo; Da Silva-Sauer, Leandro; Sancha-Ros, Salvador (Elseiver, 2013)
he aim of this work is to provide a navigation paradigm that could be used to control a wheelchair through a brain-computer interface (BCI). In such a case, it is desirable to control the system without a graphical interface so that it will be useful for people without gaze control. Thus, an audio-cued paradigm with several navigation commands is proposed. In order to reduce the probability of misclassification, the BCI operates with only two mental tasks: relaxed state versus imagination of right hand movements; the use of motor imagery for navigation control is not yet extended among the auditory BCIs. Two experiments are described: in the first one, users practice the switch from a graphical to an audio-cued interface with a virtual wheelchair; in the second one, they change from virtual to real environments. The obtained results support the use of the proposed interface to control a real wheelchair without the need of a screen to provide visual stimuli or feedback
Keywords: Brain–computer interface(BCI); Navigation; Asynchronous; Motor imagery(MI); Mental tasks; Auditory